2006
DOI: 10.1002/cncr.21800
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the TSLC1/IGSF4 promoter is associated with tobacco smoking and a poor prognosis in primary nonsmall cell lung carcinoma

Abstract: Objective To elucidate the safety of adalimumab for rheumatoid arthritis (RA) patients with renal insufficiency, including those with end‐stage renal disease undergoing hemodialysis. Methods Sixty‐five RA patients, including 2 patients undergoing hemodialysis, treated with adalimumab in our hospital from December 1, 2008 to June 30, 2011 were retrospectively analyzed. Renal function was evaluated by the estimated glomerular filtration rate (eGFR) calculated from the Cockcroft‐Gault formula at the start and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 45 publications
7
60
2
Order By: Relevance
“…IGSF4 gene, a novel immunoglobulin (Ig)‐like intercellular adhesion molecule located on chromosome 11q23, was first characterized as a tumor suppressor of non‐small‐cell lung cancer. Methylation of the gene was found to be associated with poor survival in non‐small‐cell lung carcinoma 30. In accordance with prior research, univariate survival analysis in this study demonstrated that progression‐free survival was found to be significantly shorter for patients with IGSF4 methylation compared to those without IGSF4 methylation.…”
Section: Discussionsupporting
confidence: 90%
“…IGSF4 gene, a novel immunoglobulin (Ig)‐like intercellular adhesion molecule located on chromosome 11q23, was first characterized as a tumor suppressor of non‐small‐cell lung cancer. Methylation of the gene was found to be associated with poor survival in non‐small‐cell lung carcinoma 30. In accordance with prior research, univariate survival analysis in this study demonstrated that progression‐free survival was found to be significantly shorter for patients with IGSF4 methylation compared to those without IGSF4 methylation.…”
Section: Discussionsupporting
confidence: 90%
“…No evidence for hypermethylation of the CADM1 promoter region in neuroblastoma To investigate whether hypermethylation of the CADM1 promoter is involved in regulating CADM1 expression levels in neuroblastoma, eight CpG sites located in the promoter region that have been demonstrated to be methylated in several tumours (Fukami et al, 2003;Steenbergen et al, 2004;Kikuchi et al, 2006) were tested for methylation by bisulphite sequencing. Hypermethylation was defined as methylation of a CADM1 is a tumour suppressor gene in neuroblastoma S Nowacki et al specific CpG site in >50% of the clones sequenced.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the molecular mechanism underlying transcriptional repression in these cases is unlikely to be hypermethylation. Although we cannot rule out the possibility that hypermethylation of a distinct set of CpG sites in the promoter region might have occurred as described for cervical cancer (Li et al, 2005), the eight CpG sites chosen for our analysis have been considered to be representative for global hypermethylation in several studies (Fukami et al, 2003;Steenbergen et al, 2004;Kikuchi et al, 2006). Nevertheless, hypermethylation can be indicative, but is not necessarily involved in downregulation of CADM1 expression as suggested from previous analysis of two prostate cancer cell lines (Fukuhara et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations